Preliminary Study of Solar Energy Utilization for Rural Electrical Energy. Case Studies in Central Kalimantan - Andrianshah Priyadi; Budi Sutrisno; Setya Sunarna; Fariz Maulana Rizanulhaq; Wulan Erna Komariah; Adjat Sudradjat; Dian Khairiani (Department of Electrical Engineering ITS and FORTEI, 2023)
Indonesia gradually improves the electricity system's reliability and reaches the areas which contain frontier, outermost and underdeveloped areas by utilizing local energy potential. It can be done independently and in groups to meet the need for electrical energy in remote villages. Electrical power is obtained from generators and solar modules installed in each resident's house, where the capacity and quality are minimal. The initial study was completed in 2019 and took place in Central Kalimantan province, divided into three districts consisting of ten villages. Access to the village is a challenge in satisfying electrical energy needs, so alternatives are needed to meet the demands of electrical energy for areas that are difficult to reach by the electricity network. The solar power plant is one alternative to using new and renewable energy. The State Electric Company is an Indonesian state-owned enterprise that generates, transmits, and distributes electric power which also responsible to provide the electricity network in Indonesia. This study's village information was obtained from the survey results, village energy needs, and costs incurred when the solar power system was installed.